Laparoscopic spleen-preserving pancreatic resection for epidermoid cyst in an intrapancreatic accessory spleen: case report and literature review - Zhou B; Zhang Q; Zhan C; Ding Y; Yan S (Dove Medical Press, 2018)
Bo Zhou,1 Qiyi Zhang,1 Canyang Zhan,2 Yuan Ding,1 Sheng Yan1 1Division of Hepatobiliary and Pancreatic Surgery, Department of Surgery, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Neonatology, Children’s Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China Introduction: An epidermoid cyst in an intrapancreatic accessory spleen (ECIPAS) is a rare non-neoplastic cyst, typically occurring in the pancreatic tail. It is difficult to preoperatively differentiate ECIPAS from other types of pancreatic neoplastic cysts.Case presentation: We herein report a case of a 32-year-old man with a cystic tumor in the tail of the pancreas. The patient underwent a laparoscopic spleen-preserving distal pancreatectomy, and histological examination revealed the presence of ECIPAS. In addition, we also performed a literature review of 42 case reports of ECIPAS.Conclusion: Although the preoperative diagnosis of ECIPAS is relatively difficult, familiarity with the imaging features, the clinical presentation and the location of the cyst could lead to a correct preoperative diagnosis of ECIPAS, which might thereby reduce the number of unnecessary resections. Keywords: epidermoid cyst, accessory spleen, pancreas